Programmable Nanomedicine and Multifunctional Vectors for the Selective Targeting of HIV-1 Reservoirs: Toward a Next-Generation Shock & Kill Strategy - Barack Ndenga (Publisher, 2026)
The persistence of replication-competent HIV-1 within latent cellular reservoirs constitutes the definitive barrier to a cure.While antiretroviral therapy suppresses active replication, it cannot engage transcriptionally silent proviruses. This review articulates a paradigm shift from systemic pharmacology to precision-targeted intervention, enabled by programmable nanomedicine. We examine the conceptual and material foundations of multifunctional nanovectors engineered to execute the sequential steps of "Shock & Kill"—latency reversal, immune engagement, and targeted cell elimination—within a single, spatiotemporally controlled system. These platforms offer a transformative solution to the core limitations of conventional approaches, promising to translate the Shock & Kill hypothesis from a blunt empiric strategy into an orchestrated therapeutic reality. Keywords : HIV cure,Latent reservoir,Shock and Kill,Nanomedicine, Targeted drug delivery, Multifunctional nanoparticles, Programmable release, Combinatorial therapy,Stimuli-responsive,Cell-specific targeting,Viral persistence,Lymphoid tissue, CD4+ T cells, Precision medicine, Translational research
The persistence of latent,replication-competent HIV-1 reservoirs remains the definitive barrier to a cure. This conceptual review argues for a paradigm shift from systemic drug delivery to precision-guided intervention, enabled by programmable nanomedicine. We critically examine the design and function of multifunctional nanovectors engineered to execute the complete "Shock & Kill" sequence—targeted latency reversal, immune engagement, and specific elimination of reactivated cells—within a single, spatiotemporally controlled system. By integrating stimuli-responsive materials, combinatorial drug payloads, and surface targeting ligands, these platforms directly address the core limitations of conventional approaches: poor reservoir penetration, lack of specificity, and toxic off-target effects. This work synthesizes a roadmap for translating nanomedicine from a promising technological framework into an orchestrated therapeutic reality capable of dismantling viral persistence.